The fragments of Hellenistic oratory: introduction, text, and commentary - Berardi, R (2020)
Contrary to the idea that most of the fragments of ancient authors have been already collected and edited, a scholar interested in Hellenistic history and literature may find it surprising that a collection of fragments of Hellenistic orators – or oratory – is not something we could at the moment find on the shelves of a library. For a discipline like ancient literature, which is fragmentary at its core, this seems a surprising gap: we can find collections of fragments for poets of all sorts, for dramatists, historians, geographers, orators (Attic, Roman), and for so many more literary genres that it would be natural to assume that, if we do not have a collection of fragments for a certain genre in a certain period, it must be because nothing at all of it has survived.